SA-2 Representation of Various Systematic Disruptions within the Patients Handled at “Klinik Hewan Jogja” between January and June 2018 - Ida Tjahajati; Adellyna Chrissandra; Anggi D Prayitno; Begum F R Aditya; E Rrarindah; L Rifiyanta; M A Candra; T A Widiastuti; S I Astuti (Hemera Zoa, 2018)
Various diseases or disruption could affect all of the patients handled at any clinic or hospital. The health problems would be varied, depending on the disease or systemic disruption that ailed the patient. This research aims to figure out the spread of said health problems in the patients handled at Klinik Hewan Jogja between January and June 2018.A numerical representation of afflictions that ails the patients in a clinic or a hospital during a period of time would provide the information needed to anticipate several diseases, facilitate easier treatment and follow-up actions for certain ailments, offer prevention methods, and lastly to yield data for clients' education. The data gathered is also vital to give a general picture the problems that frequent a certain area, thus imparting important information to all other clinics or hospitals in the said region.